Estudos estruturais e de atividades biológicas do soyuretox, um peptídeo derivado de urease. Zebrafish (Danio rerio) como modelo de estudo do peptídeo - Kappaun, Karine (2018)
Ureases (urea amidohydrolases, EC 3.5.1.5) are nickel-dependent enzymes, widely spread in bacteria, fungi and plants, which catalyze the hydrolysis of urea to ammonia and carbon dioxide. Jaburetox is a peptide derived from a urease isoform of the Canavalia ensiformis plant. Structurally, jaburetox is an intrinsically disordered peptide, demonstrated by bioinformatics tools, and experimentally, by circular dichroism (CD) and nuclear magnetic resonance (NMR). Several biological properties of jaburetox have already been described, such as insecticidal activity, ability to interact with lipid bilayers, fungitoxic effect, among others. Soyuretox is a peptide colinear to jaburetox derived from the soybean ubiquitous urease. One of the objectives of this thesis was to carry out structural studies of the soyuretox peptide by CD and NMR, which revealed its intrinsically disordered nature and that its secondary structure content is modified in the presence of SDS micelles. Biological properties of soyuretox were evaluated. The peptide has entomotoxic activity, inducing aggregation of hemocytes from Rhodnius prolixus, the vector of Chagas disease, both in vivo and in vitro. The fungitoxic effect of soyuretox on yeast Candida albicans involves the production of superoxide anions, and the peptide was immunolocalized on the surface of the yeast. Finally, the behavioral and morphological effects of soyuretox on zebrafish larvae (Danio rerio) were evaluated, aiming to deepen the understanding of the mechanism of toxic action and the toxicological profile of this molecule, which presents biotechnological potential as a biopesticide.